El humano como recurso de las organizaciones hipermodernas: resonancias del poder gerencialista - Braz, Matheus Viana [UNESP]; Hashimoto, Francisco [UNESP] (My University, 2014)
Nowadays, the current work perspective is characterized by a management economy in which the accounting and financial considerations overlap the human and social considerations. Therefore, there is a creation of a social imaginary dominated by a capitalist and utilitarist logic. With this in mind, we intend, in this theoretical-reflexive study, learn the power resonances and managerialist ideology for the included subjects in the hypermodern organizations. This way, this research was constructed by the light of Psichosociology. The reading through these approaches emphasizes the imaginary dimension, intersubjective and group of the organizations, contributing to the understanding of job relations and worker's mental health.

El panorama actual laboral se caracteriza por una economía gestionaria, en la cual las consideraciones contables y financieras se sobreponen a las consideraciones humanas y sociales. Hay, con efecto, la creación de un imaginario social dominado por una lógica capitalista y utilitaria. En ese sentido, pretendemos, en este trabajo teórico-reflexivo, aprehender las resonancias del poder e ideología gerencialista para los sujetos insertados en las organizaciones hipermodernas. Para eso, esta investigación ha sido construida bajo la óptica de la Psicosociología, abordaje que enfatiza la dimensión imaginaria, intersubjetiva y grupal de las organizaciones, contribuyendo para la comprensión de las relaciones de trabajo y de la salud mental de los trabajadores.
The human as a resource of the hypermodern organizations: resonances of managerialist power
Keywords: Hypermodernity; Managerialist power; Hypermodern organizations; Hipermodernidad; Poder gerencialista; Organizaciones hipermodernas